Role of financial development in the export performance of a landlocked developing country: The case of Nepal - Ramesh Paudel; Majed Alharthi (Cogent Economics & Finance, 2021)
This paper, using the most recent index of financial development as developed in an IMF publication by Svirydzenka, examines the role of overall financial development, financial institutions, and financial markets in the export performance of Nepal employing the Autoregressive distributed lag (ARDL) approach of cointegration using the annual datafrom 1980 to 2017. The results show that financial development does not have a strong long-run positive relationship with the export performance of Nepal. Financial institutions and financial markets also indicate a negative association with exports. Therefore, it can be suggested based on the results that there is a need for developing strategies for the proper financial development improving the financial institution quality, and widening the financial market targeting to facilitate more meaningfully to the exporters and manufacturers to boost export performance.
Keywords: O16; O40; C23; 330; ARDL approach of cointegration; export performance; Financial development